The Chimeric Propeller Flap - Hallock, Geoffrey G. (Seminars in Plastic Surgery, 2020)
A chimeric flap consists of multiple discrete tissues or flaps connected only by a common source vessel. Each component must have an independent source of circulation. Rotation of any included part only about its specific vascular supply, such as done with a propeller flap, would be possible. These characteristics, whereby the chimeric flap concept and propeller flap concept are combined, would result in a chimeric propeller flap. Such a choice will enhance overall flap insetting capabilities and versatility, while often limiting the reconstructive need to but a single donor site!
Keywords: chimeric flap; propeller flap; composite flap; perforator flap